1996
DOI: 10.1101/gad.10.12.1491
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian p50Cdc37 is a protein kinase-targeting subunit of Hsp90 that binds and stabilizes Cdk4.

Abstract: CDC37, an essential gene in Saccharomyces cerevisiae, interacts genetically with multiple protein kinases and is required for production of Cdc28p/cyclin complexes through an unknown mechanism. We have identified mammalian p50Cdc37 as a protein kinase-targeting subunit of the molecular chaperone Hsp90. Previously, p50 was observed in complexes with pp60v-src and Raf-1, but its identity and function have remained elusive. In mouse fibroblasts, a primary target of Cdc37 is Cdk4. This kinase is activated by D-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
450
2
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 462 publications
(494 citation statements)
references
References 47 publications
40
450
2
1
Order By: Relevance
“…Similar to most of the Hsp90 client kinases, Cdks are recruited to Hsp90 by Cdc37 (Caplan et al 2007). Interestingly, early studies devoted to the interactions between Hsp90/Cdc37 and the members of Cdk family identified Cdk4 and Cdk6, whereas other Cdks failed to interact with Hsp90/Cdc37 (Stepanova et al 1996;Lamphere et al 1997). Only recently, Cdk2 has been shown to be a genuine client kinase of Hsp90/Cdc37 (Prince et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to most of the Hsp90 client kinases, Cdks are recruited to Hsp90 by Cdc37 (Caplan et al 2007). Interestingly, early studies devoted to the interactions between Hsp90/Cdc37 and the members of Cdk family identified Cdk4 and Cdk6, whereas other Cdks failed to interact with Hsp90/Cdc37 (Stepanova et al 1996;Lamphere et al 1997). Only recently, Cdk2 has been shown to be a genuine client kinase of Hsp90/Cdc37 (Prince et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…p50 is a kinase specific co-chaperone and is thought to assist in the transfer of kinases to Hsp90 (Grammatikakis et al, 1999;Lee et al, 2002;Stepanova et al, 1996). Domain mapping has shown that p50's N-terminal domain is critical for binding kinases whereas the middle and C-terminal domains interact with Hsp90 (Grammatikakis et al, 1999;Roe et al, 2004;Shao et al, 2003).…”
Section: P50 a Kinase Specific Co-chaperone Also Traps Hsp90 In An mentioning
confidence: 99%
“…Other kinases may be stabilized by additional intramolecular domains and/or by regulatory partner proteins that bring stability along with substrate specificity 23 . For instance Cdk4 binds initially to Hsp90 and Cdc37 until encountering cyclin D1 and forming a Cdk4-Cyclin D1 complex sufficiently stable to be independent of further chaperone interaction 25 . Other kinases such as the oncogenic c-erb-B2 bind persistently to chaperone complexes even in the active form (reviewed 2 ).…”
Section: Structural Mechanisms Of Cdc37-kinase Interactionmentioning
confidence: 99%